Organised trauma systems and designated trauma centres for improving outcomes in injured patients - Mwandri, Michael (2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of organised trauma systems and designated trauma centres for improving outcomes in injured patients, specifically patient outcomes and adverse effects or harms.